Penerapan Senam Kaki Diabetik Terhadap Sensitivitas Kaki Penderita DM di Desa Sangkrah Pasar Kliwon Surakarta - Bagus Novanda Dwi Prasetyo; Irma Mustika Sari (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Diabetes Mellitus is a metabolic disease that has hyperglycemia caused by abnormalities in insulin secretion, insulin performance, or both. DM will cause several complications, one of which is sensory neuropathy or damage to sensory nerve fibers which causes DM patients to experience decreased foot sensitivity. The number of DM sufferers at the Sangkrah Health Center in 2022 was 2,404 cases. To describe the results of the implementation before and after the application of diabetic foot exercises on foot sensitivity in patients with diabetes mellitus. This study used a descriptive design by observing foot sensitivity in 2 respondents, carried out in the morning for 1 week with 2 meetings each meeting 15 minutes. The instruments used were observation sheets, monofilament test tools, and newspapers. There was an increase in foot sensitivity scores after diabetic foot exercises were carried out for 2 days in 1 week each meeting 15 minutes to both respondents. The application of diabetic foot exercises can be useful for increasing foot sensitivity in both respondents with diabetes mellitus.